Beispiel Nr: 05
$ D_h=\begin{array}{|cc|}a1\ & b1 \\ a2&b2 \\ \end{array}= a1 \cdot b2 -b1 \cdot a2 \\ D_x=\begin{array}{|cc|}c1\ & b1 \\ c2&b2 \\ \end{array}= c1 \cdot b2 -b1 \cdot c2 \\ D_y=\begin{array}{|cc|}a1\ & c1 \\ a2&c2 \\ \end{array}= a1 \cdot c2 -c1 \cdot a2\\ x=\frac{D_x}{D_h} \\ y=\frac{D_y}{D_h} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +3 y =9\\ 3 x -2 y = -6 \\ \\ \\ \\ \textbf{Rechnung:} \\ D_h=\begin{array}{|cc|}1\ & 3 \\ 3&-2 \\ \end{array}= 1 \cdot \left(-2\right) -3 \cdot 3=-11 \\ D_x=\begin{array}{|cc|}9\ & 3 \\ -6&-2 \\ \end{array}= 9 \cdot \left(-2\right) -3 \cdot \left(-6\right)=0 \\ D_y=\begin{array}{|cc|}1\ & 9 \\ 3&-6 \\ \end{array}= 1 \cdot \left(-6\right) -9 \cdot 3=-33 \\ \ x=\frac{0}{-11} \\ x=0 \\ y=\frac{-33}{-11} \\ y=3 \\ L=\{0/3\}\\ \, $